(untitled) (Bioagro, 2020)
The soil properties are a vital support for development of plants and organisms, and affect the crop productivity; nevertheless, the agriculture managing can change the soil quality. The objective of this research was to characterize properties of the soil in 13 productive units (PU) in the Center of Agroindustrial Formation, Campoalegre County, Huila State, Colombia, and their relationship with the production system. Samples were taken at three representative points of each PU, to a depth of 60 cm, from which organic matter (OM), pH, electrical conductivity, bulk density (Bd) and total porosity were determined. The software InfoStat was used for data analysis based on Fisher LSD variance test and a multivariate conglomerate method. It was found that soils were heterogeneous, attributed to the variability of management and established crops. The main differences were found in the degree of soil compaction, due to the higher Da in the system with coffee crop, and in the higher OM content observed in the agroforestry system with passion fruit, banana and cocoa crops. Cocoa productive unit and the agroforestry system, conformed by fruit crops and cocoa, were associated by variables of pH and organic matter with impacts on soil physical and chemical properties.